Pengembangan Media Pembelajaran Interaktif PowerPoint Pada Materi Norma Dalam Kehidupanku Kelas V Sekolah Dasar - Winda, Winda; Nukman, Muhamad (Cetta: Jurnal Ilmu Pendidikan, 2025)
Learning media that does not support the learning process is one of the causes of students feeling bored with learning. Therefore, teachers need to use learning media that can support the learning process, one of which is interactive learning media Powerpoint. This study aims to describe the development process and assess the feasibility and effectivene sof interactive PowerPoint learning media for the Norma dalam Kehidupanku material for grade V students of SDN 160 Pekanbaru. The research method used is research and development using a qualitative and quantitative approach of the Research and Development (R&D) type with a 4D design. This development research was conducted using a four-stage procedure, consisting of the definition stage (define), the planning stage (design), the development stage (develop), and the dissemination stage (disseminate). The main data sources in this study consisted of 6 material expert validators, language experts, and design experts as well as teachers and students of class VA. The research instrument was in the form of a validation questionnaire sheet for material experts, language experts, and design experts as well as a questionnaire for teacher and student responses. Based on the validation results, it shows that this learning media meets the eligibility standards, with the percentage of eligibility from material experts of 85,5%, language experts 85,8%, and design experts 85,2%, all in the category of feasible or valid. Meanwhile, the response from the teacher showed a level of eligibility of 95% and the response from students was 95.7%, both of which were in the very feasible category.